Social norms in the corporate debt market: European Evidence - Pany, Christian (My University, 2019)
The purpose of this thesis is to study the relationship between corporate social responsibil-ity and the cost of debt and to investigate if social norms play a role in the corporate debt market. This is done by researching the impact of CSR on the interest rate spread of bank loans and yield spread of corporate bonds in Europe. The sample includes 1711 bank loans, 742 Euribor-denominated and 969 Libor-denominated, and 645 corporate bonds of 18 European countries in the period 2003 - 2017. The relationship is tested with OLS re-gression investigating four measures of CSR with a set of explanatory variables to control for company specific criteria as well as loan and bond characteristics. The empirical findings suggest that for Euribor-denominated bank loans the different ESG scores, except for the governance aspect, decrease the interest rate spread by an average of 4% with a 10-point increase in the respective score. Furthermore, companies with the highest CSR score pay up to 30% lower interest rate, with all four aspects having statistical significance. For Libor-denominated loans, this impact disappears, and it seems as if the relationship with corporate social responsibility vanishes. This opposing results for Euribor and Libor loans are interesting, because this kind of research has not been conducted pre-viously, and signals that CSR is only prevalent in the Eurozone private debt market as op-posed to debt markets in other currencies In the public debt market, yield spreads of corporate bonds experience a similar decrease as Euribor loans for the environmental and social aspect, although the governance aspect has the opposing effect and increases the yield. To conclude, the private and the public debt market appear to have a similar relationship with CSR, though only applicable to Eu-ribor loans. This confirms the stakeholder and risk mitigation theory for the overall, social and environmental score, and the overinvestment theory for the governance aspect. The results highlight that lenders in general value corporate social responsibility as risk mitigating and view it as a long-term investment. This provides information to companies on how they can decrease their cost of debt by implementing specific aspects of corporate social responsibility in their business activities.
Keywords: CSR; ESG; cost of debt; bank loans; corporate bond; fi=Laskentatoimi ja rahoitus|en=Accounting and Finance|; fi=Master's Degree Programme in Finance|